Innate lymphoid cells in inflammatory arthritis - Weiting Fang; Yuanyuan Zhang; Zhu Chen (Arthritis Research & Therapy, 2020)
Abstract Aberrant activation and dysregulation of immune system is a common feature of many forms of inflammatory arthritis. Since their identification as a distinctive population of leukocytes, innate lymphoid cells (ILCs) have been considered crucial in maintaining tissue homeostasis and bridges between innate and adaptive immune system. Altered ILCs’ subset distribution and function have been observed in a variety of autoimmune and chronic inflammatory diseases and suggest a subset-specific role of ILCs in the pathogenesis of immune-mediated inflammation. In this review, we focus on the current knowledge of ILC subset and their role in inflammatory arthritis, including rheumatoid arthritis (RA), ankylosing spondylitis (AS), psoriatic arthritis (PsA), enteropathic arthritis, and other seronegative spondyloarthritis. By better understanding the biology and function of ILC subset in different disease settings, new therapeutic interventions can be anticipated by modulating dysregulated ILC responses toward promoting resolution of inflammation.